(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
Landslides have become more frequent, driven by climate change that results in heavy rainfall, combined with inadequate occupation of urban areas. These phenomena have negative consequences for society, causing material damage and affecting people’s safety. It is important to identify areas susceptible to landslides in order to implement measures to mitigate the associated risks. Thus, this work aims to determine the level of landslide risk of a slope located on Matildes Borges da Rocha Street and Uruguay Street in the São Cristóvão neighborhood, in the city of Teófilo Otoni, Minas Gerais. The methodology adopted included a field survey, photographic records, annotations on field files, and the application of the methodological script for risk analysis and mapping of risk areas in slope and lowland sectors, with a focus on landslides, recommended by the Ministry of Cities in 2007. After the analyses, the results revealed that the study area has a degree of R4 (very high) risk. Given this scenario, there is a need to implement mitigating measures and intervention plans to ensure the physical and property safety of the region’s residents.